Hubungan Pterigium dengan Kejadian Dry Eye pada Masyarakat di Kabupaten Tojo Una-Una, Sulawesi - Anggraeni Adiwardhani; Husnun Amalia; Noviani Prasetyaningsih; Riani Witjaksana; Rizky Eka Adeliani (Jurnal Biomedika dan Kesehatan, 2026)
Background Indonesia is a tropical country exposed to ultraviolet (UV) rays year-round, particularly in Central Sulawesi Province, which lies on the equator. Tojo Una Una Regency is located in this province, and the majority of its residents work as fishermen, who are frequently exposed to UV radiation, a risk factor for pterygium and dry eye. This profession has the highest incidence of pterygium, reaching 15.8%. This study will analyze the relationship between pterygium and dry eye. Methods The study design was cross-sectional with consecutive non-random sampling. A questionnaire was used to assess characteristics. Pterygium was diagnosed through an anterior segment examination by a general practitioner, followed by a double-blind ophthalmologist to assess the degree, location, and whether the pterygium was single or double-headed. The degree and diagnosis of dry eye were confirmed using the OSDI questionnaire. Results The study involved 400 respondents, and the prevalence of pterygium reached 85.25%, with cases predominantly bilateral (66.5%), single-headed (70.25%), female (72.75%), 26-45 age group (49.25%), and those working outdoors (77%). DES cases were found in 54.25%, with the majority being severe DES. A chi-square test showed a relationship between dry eye and pterygium (p<0.001). Conclusions There was a significant relationship between DES severity and pterygium incidence (p<0.001).